Be-TeaM: An Italian real-world observational study on second-line therapy for EGFR-mutated NSCLC patients. (February 2020) - Reale, Maria Lucia; Chiari, Rita; Tiseo, Marcello; Vitiello, Fabiana; Barbieri, Fausto; Cortinovis, Diego; Ceresoli, Giovanni Luca; Finocchiaro, Giovanna; Romano, Gianpiero Diego; Piovano, Pier Luigi; Del Conte, Alessandro; Borra, Gloria; et al.
Highlights: Few data document the real-world strategies to manage advanced NSCLC after PD. Be-TeaM provides the first snapshot of current practices in this setting in Italy. Most patients were screened for T790M and had a post-PD therapy chosen. However, testing in clinical practice is not always feasible. This precludes many patients from receiving osimertinib after first-line TKI failure. Abstract: Objectives: Molecular diagnostics and care of non-small cell lung cancer (NSCLC) are continuously evolving. Few data document the current strategies to manage advanced NSCLC patients beyond progression in clinical practice. Patients and methods: Be-TeaM is an Italian multi-center observational study conducted on consecutive EGFR-mutated stage IV NSCLC patients, progressed during/after a first-line EGFR-TKI. It consists of a retrospective phase, from first-line EGFR-TKI therapy start until study entry (i.e. beginning of the diagnostic process), and a prospective phase, until treatment choice or for 3 months if no therapy was prescribed. Primary objective was to describe the diagnostic and therapeutic approaches adopted after progression in a real-world setting. Results: Of 308 patients enrolled in 63 centers from July 2017 to June 2018, 289 were included in the analysis. In first line, 53.3 % received gefitinib, 32.5 % afatinib and 14.2 % erlotinib. The testing rate (i.e. rate of all patients undergone any biopsy -liquid and/or tissue- for the T790 M detection) was 90.7 %, with liquid biopsy being the most frequently executed. Of 262 biopsied patients, 64.5 % underwent only 1 liquid biopsy, 10.7 % only 1 tissue biopsy and 18.3 % >1 biopsy, both liquid and solid in 85.4 %. The T790M positivity rate was 45.3 %; of 166 patients undergone only a liquid biopsy and tested for the mutation, 39.8 % were T790M+ and 60.2 % T790M-/undetermined. By the observation end, 87.9 % patients had a post-progression treatment chosen, osimertinib being the most frequent among the T790M+. Conclusion: Be-TeaM provides the first snapshot of current practices for the management of NSCLC patients beyond progression in Italy; in clinical practice, assessing the T790M status is not always feasible.